Cardiovascular Health - World Bank (Washington, DC, 2012)
In 2001, 16.6 million deaths globally were due to cardiovascular diseases (CVD); this figure will increase to 25 million by 2025. The two leading causes of death worldwide are cardiovascular coronary heart disease (which causes heart attack and heart failure) and cerebrovascular disease (which causes stroke). The direct and indirect costs of CVD are high: enormous health care costs and productivity/income losses. Of all global deaths from CVD, 65 percent occur in developing countries. This will increase to 75 percent by 2025. By then, cardiovascular disorders will be the biggest cause of lost disability-adjusted life years (DALYs) worldwide, and the second leading cause of DALY loss in developing countries. In developing countries, cardiovascular diseases predominantly affect people of working age (30-64 years). Death and disability in middle age has major social and economic consequences Prevention or treatment of risk factors for CVD is effective and sustainable in the long run. The risk of CVD can be reduced quickly and substantially with successful preventive practices. This also has a favorable impact on other non-communicable diseases (NCDs) that share the same risk factors. Treatment of established CVD is expensive and resource intensive. Unregulated private health systems tend to direct a large proportion of resources to costly cardiovascular technologies available only to the wealthy few.